Glucose turnover in pregnant women with acute malaria. - Davis, T; Suputtamongkol, Y; Spencer, J; Wilson, S; Mekhton, S; Croft, K; White, N (1994)
1. Hypoglycaemia is a serious complication of falciparum malaria, especially in pregnant patients. To investigate malaria-associated changes in glucose metabolism in pregnancy, steady-state [6,6-2H2] glucose turnover and clearance were measured in 10 women (eight with uncomplicated falciparum malaria and two with vivax malaria at 16-30 weeks gestation) before treatment, after intravenous quinine infusion (patients with falciparum malaria) and in convalescence. 2. Admission basal plasma glucose concentrations were higher than those in convalescence [median (range); 4.8 (3.6-7.0) versus 4.0 (3.6-4.6) mmol/l, P = 0.02], and there was a significant fall during initial quinine treatment in patients with falciparum malaria [5.0 (4.3-7.6) to 3.6 (3.2-5.4) mmol/l, P < 0.01]. Basal plasma insulin levels were comparable at presentation and follow-up (P = 0.35) and rose an average of only 2m-units/l during quinine infusion (P < 0.05). Pretreatment glucose turnover rates [3.37 (2.57-4.16) mg min-1 kg-1] were comparable with those found in a previously reported study of non-pregnant severely ill patients [3.22 (2.12-4.82) mg min-1 kg-1, n = 11] and correlated significantly with the admission parasitaemia (P < 0.025). In the eight patients with falciparum malaria, there was a significant fall in turnover during intravenous quinine infusion [3.42 (2.58-4.16) to 2.66 [1.94-3.94) mg min-1 kg-1] whereas clearance did not change significantly.(ABSTRACT TRUNCATED AT 250 WORDS)